A ética, a estética e o dígito: a comunicação e a lógica algorítmica na construção da subjetividade - Pessoa Neto, Hermínio (2024)
In the face of rapid technological advancement, in-depth studies on the social, economic, and political impacts of Information and Communication Technologies (ICTs), as well as on societal mental health, are becoming increasingly necessary. In the current context of cyberculture, digital social media, driven by economic interests, play a central role in mediating and transforming perceptions related to aspects such as beauty, humor, behavior, affection, and reliability. These issues are influenced by the global trend of digitalization and the growing platformization of media. This master's research proposes an analysis of contemporary morality and the effects of a profit-oriented system. Its main objective is to promote a reflection on subjectivity, understood as a set of symbols, meanings, ideas, and emotions that permeate individuals, groups, and institutions, in light of new cultural, economic, and algorithmic perspectives in communication. The study explores the concept of subjectivity based on the synthesis of Plato's ideal of the good, the beautiful, and the true. The relationship between these philosophical pillars and the available resources on the Instagram digital application are investigated, including aspects such as engagement (reach, likes, and comments), filters, and followers. With a qualitative approach, the dissertation revisits classic works in the fields of Communication, Philosophy, Sociology, History, Psychoanalysis, and Psychology, aiming to understand how changes in communication impact cultural imagination and human experience in their social and emotional dimensions. The theoretical foundation is based on Lucia Leão's concept of cartography of imaginaries and seeks to establish dialogues with thinkers such as Michel Foucault, Jean-Paul Sartre, Shoshana Zuboff, and Byung Chul Han